A reconfigurable test platform to experiment with wireless heterogeneous networks in a laboratory. (6th July 2010) - Dini, Paolo; Portoles-Comeras, Marc; Nin-Guerrero, Jaume; Mangues-Bafalluy, Josep; Dai, Lillian; Addepalli, Sateesh
A large number of wireless technologies and networks have been introduced in the telecommunication world during the last few years. Many protocols and applications (e.g., TCP, VoIP) are not specifically designed for such a variety of wireless protocols; therefore they require a deeper analysis to understand their behaviour over those radio protocols. Performance analysis in close-to-real environment represents a valid method to evaluate and model the behaviour of such protocols and applications for their improvement. This paper presents a wireless heterogeneous testbed that allows experimentation of WLANs and cellular networks in a laboratory. The paper describes also the assessment and the calibration of the testbed. It presents an extensive comparison with a commercial 3G network. Finally, the paper also presents two case studies in order to highlight the benefits of conducting experimental research in an in-lab fully controlled platform.